Meaning-making and interpretation through personal mandalas in the context of visual literacy. Issue 3 (2nd October 2022) - Qureshi, Amna; Sarantou, Melanie; Miettinen, Satu
Abstract: This research investigates the significance of creative freedom and self-expression through the visual analysis of artworks produced in a workshop under the theme 'Visual Literacy'. This multi-layered qualitative study presents the findings from a participatory arts-based research approach that elicits students' creative expression through their personal mandalas. Artworks collected from this creative process were assessed using the interpretive phenomenological analysis method whereas the Common European Framework of Reference for Visual Literacy (CEFR-VL) was used as an assessment tool. Supporting youth through arts-based interventions and motivating them to communicate their feelings and perceptions can be an integral part of students' creative development. Hence, as the focus of the study, this paper aims to illustrate the youths' perception, interpretation, and meaning-making through the artistic creative processes to stimulate their creative and critical thinking.